2016
DOI: 10.1007/s13670-016-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Cognitive Impairment in Older Adults with Cancer

Abstract: Aging is a risk factor for cognitive impairment as well as cancer. However, the interplay between these three entities – aging, cognition and cancer – is not well understood. Mounting evidence indicates that both cancer and cancer therapies, such as chemotherapy, can negatively affect cognition and that older adults with pre-existing cognitive impairment may be more susceptible to cognitive decline with therapy than younger patients. For an older adult, decline in cognition may significantly compromise their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 51 publications
(46 reference statements)
0
63
1
Order By: Relevance
“…70 SEER Medicare studies suggest that the estimated prevalence of dementia in cancer patients age 65 and over ranges from 3.8 to 7%, 7173 although these estimates may be lower than true prevalence due to lack of reporting of these diagnoses within Medicare claims. 70 Few studies have examined how a prior diagnosis of MCI or dementia specifically impacts treatment decision-making for cancer and what percentage of these patients are offered various types of cancer therapies, such as surgery or chemotherapy. 70 Gupta and Lamont found that colon cancer patients with a pre-existing dementia diagnosis were more likely to be diagnosed without biopsies and less likely to be treated with curative intent, compared to non-dementia colon cancer patients.…”
Section: Risk Factors For Crcimentioning
confidence: 99%
See 1 more Smart Citation
“…70 SEER Medicare studies suggest that the estimated prevalence of dementia in cancer patients age 65 and over ranges from 3.8 to 7%, 7173 although these estimates may be lower than true prevalence due to lack of reporting of these diagnoses within Medicare claims. 70 Few studies have examined how a prior diagnosis of MCI or dementia specifically impacts treatment decision-making for cancer and what percentage of these patients are offered various types of cancer therapies, such as surgery or chemotherapy. 70 Gupta and Lamont found that colon cancer patients with a pre-existing dementia diagnosis were more likely to be diagnosed without biopsies and less likely to be treated with curative intent, compared to non-dementia colon cancer patients.…”
Section: Risk Factors For Crcimentioning
confidence: 99%
“…70 Few studies have examined how a prior diagnosis of MCI or dementia specifically impacts treatment decision-making for cancer and what percentage of these patients are offered various types of cancer therapies, such as surgery or chemotherapy. 70 Gupta and Lamont found that colon cancer patients with a pre-existing dementia diagnosis were more likely to be diagnosed without biopsies and less likely to be treated with curative intent, compared to non-dementia colon cancer patients. 71 Chemotherapy and radiation are administered less frequently to breast cancer patients with a preexisting dementia diagnosis compared to non-dementia breast cancer patients.…”
Section: Risk Factors For Crcimentioning
confidence: 99%
“…For the topic in the medication section, we observed medications to control high blood sugar [38]. The topic in the diagnosis section includes the terms related to cancer [39][40][41][42]. Table 3, set of section and history of present illness include hyperlipidemia that can be considered as a risk factor of CI [43], coronary artery disease and hypertension, which are relevant to cognitive decline [44,45].…”
Section: Topic Modeling Qualitative Analysismentioning
confidence: 99%
“…Words like edema, distress, memory, hypertension, coronary, urinary and hyperlipidemia as the potential risk factor of cognitive dysfunction was discussed [44][45][46][47]. Carcinoma, melanoma, cancer, and squamous in the last row are the terms related to cancer [39][40][41][42].…”
Section: Topic Modeling Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation